Does Size Matter? Mate Choice in Two Lekking Flies. Issue 2 (11th April 2020) - Tejeda, Marco Tulio; Arredondo, José; Díaz-Fleischer, Francisco; Pérez-Staples, Diana
Abstract: For insect pests controlled through the Sterile Insect Technique (SIT), which consists in the mass production, sterilization, and release of target insects into affected areas, sterile male mating success with wild females is the key that will reduce population levels in the next generation. Male size is assumed to be important for mating success, but often without any concrete evidence or confounded by other parameters. Here, we evaluated male size and its interaction with male origin (laboratory or wild) on female choice for two lekking species controlled through SIT, Anastrepha obliqua (Macquart) and Anastrepha ludens (Loew) (Diptera: Tephritidae). In field cages, we tested wild females mating with: large wild males competing against small wild males; large wild males against small laboratory-sterile males; and large laboratory-sterile males against small wild males. We found evidence of large male advantage for A. obliqua but no effect of male size on mating competitiveness for A. ludens . For A. obliqua large wild males had a greater mating success over small laboratory males, yet large laboratory males secured a similar amount of copulations than small wild males. For A. ludens, there was no effect of male size on mating success. We discuss why A. obliqua is sensitive to size and origin while no effect was seen in A. ludens . SIT programs should not assume that male mating success is dependent on a large size. Alternatively, when an advantage exists for large males, mass-rearing programs should stride to produce and release large males.